Changes in Gut Microbiota and Metabolites in Papillary Thyroid Carcinoma Patients Following Radioactive Iodine Therapy - Li W; Cheng F; Zhang J; Li C; Yu D; Simayijiang H; Liu H; Li S; Yan J (International Journal of General Medicine, 2023)
Wanting Li,1,* Feng Cheng,1,* Jun Zhang,1 Caihong Li,2 Daijing Yu,1 Halimureti Simayijiang,1 Haiyan Liu,2 Sijin Li,2 Jiangwei Yan1 1Shanxi Key Laboratory of Forensic Medicine, Shanxi Medical University, Jinzhong, People’s Republic of China; 2Department of Nuclear Medicine, First Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiangwei Yan; Sijin Li, Tel +86 03513985386 ; +86 03514639352, Email yanjw@sxmu.edu.cn; lisjnm123@163.comPurpose: Radioactive iodine therapy is administered through oral route, which is accumulated and absorbed in the intestine. However, its effects on the intestine remain unclear. In this study, we investigated the changes in the gut microbiota and metabolites following radioactive iodine therapy.Patients and Methods: A total of 76 stool samples from the same 38 patients were collected at the start of radioactive iodine therapy and three days following the therapy. Stool microbiota and metabolites were detected using 16S rRNA gene sequencing and liquid chromatography-mass spectrometry.Results: Enterobacteriales, Enterobacteriaceae and Escherichia-Shigella were elevated in most patients (27/38) following the therapy. The levels of 2-hydroxyundec-7-enoylcarnitine were significantly lower, whereas those of 5-dehydroavenasterol, butylisopropylamine, and salsoline-1-carboxylate were higher following the therapy. The relative abundance of Escherichia-Shigella was negatively correlated with 2-hydroxyundec-7-enoylcarnitine level (r2 = − 0.661, P = 0.009). Functional pathways were predicted to be involved in amino acid and lipid metabolism following the therapy. Particularly, phenylalanine, linoleic acid, sphingolipid, purine, and alpha-linolenic acid metabolism were the main metabolic pathways.Conclusion: Gut microbiota was disturbed following radioactive iodine therapy, with increased Escherichia-Shigella. Processes associated with energy production seems to be impacted following the therapy, with significantly decreased 2-hydroxyundec-7-enoylcarnitine level. Meanwhile, some metabolites and functional pathways may have a positive effect on intestinal homeostasis, and may be related to the repair and promotion of gut recovery following the therapy. This study provides a basic foundation to explore how radioactive iodine affects gut microbiota and metabolites, and how gut function is regulated in response to radioactive iodine therapy.Keywords: radioactive iodine, gut microbiota, Escherichia-Shigella, metabolism, thyroid carcinoma